Pilidiella tibouchinae sp. nov. associated with foliage blight of Tibouchina granulosa (quaresmeira) in Brazil - B.E.C. Miranda; R.W. Barreto; P.W. Crous; J.Z. Groenewald (IMA Fungus)
Tibouchina granulosa (Melastomataceae), Brazilian glorytree (Brazilian common name – quaresmeira), a common tree of the Atlantic Forest of Brazil, is widely used as an ornamental for its violet or pink blossoms. Little is known about fungal diseases affecting this species, although these represent a known limitation for its cultivation in nurseries. Among these there is a foliage blight that occurs in combination with distortion of branch apices and die-back. A consistent association of a species of Pilidiella with the diseased tissues was observed. The fungus was isolated in pure culture and based on its morphology and DNA phylogeny, we conclude that it represents a new species, for which the name Pilidiella tibouchinae is introduced.